Comparison of fracture-load values of cantilevered FDPs - Ohlmann, Brigitte; Dittmar, Alexander; Rues, Stefan; Rammelsberg, Peter (Acta odontologica Scandinavica, 2013)
Evaluation of the effect of different framework designs and of fatigue on the fracture-load values of cantilevered fixed dental prostheses (FDPs). The load values were compared with those for lithium disilicate ceramic and metal-ceramic FDPs